Delay from biopsy to radical prostatectomy influences the rate of adverse pathologic outcomes. Issue 10 (21st March 2015) - Berg, William T.; Danzig, Matthew R.; Pak, Jamie S.; Korets, Ruslan; RoyChoudhury, Arindam; Hruby, Gregory; Benson, Mitchell C.; McKiernan, James M.; Badani, Ketan K.
Abstract : BACKGROUND: We sought to determine maximum wait times between biopsy diagnosis and surgery for localized prostate cancer, beyond which the rate of adverse pathologic outcomes is increased. METHODS: We retrospectively reviewed 4, 610 patients undergoing radical prostatectomy between 1990 and 2011. Patients were stratified by biopsy Gleason score and PSA value. For each stratification, χ 2 analysis was used to determine the smallest 15‐day multiple of surgical delay (e.g., 15, 30, 45…180 days) for which adverse pathologic outcomes were significantly more likely after the time interval than before. Adverse outcomes were defined as positive surgical margins, upgrading from biopsy, upstaging, seminal vesicle invasion, or positive lymph nodes. RESULTS: Two thousand two hundred twelve patients met inclusion criteria. Median delay was 64 days (mean 76, SD 47). One thousand six hundred seventy‐five (75.7%), 537 (24.3%), and 60 (2.7%) patients had delays of <=90, >90, and >180 days, respectively. Twenty‐six percent were upgraded on final pathology and 23% were upstaged. The positive surgical margin rate was 24.2% and the positive lymph node rate was 1.1%. Significant increases in the proportion of adverse pathological outcomes were found beyond 75 days in the overall cohort ( P = 0.03), 150 days for patients with Gleason <=6, and PSA 0–10 ( P = 0.038), 60 days for patients with Gleason 7 and PSA >20 ( P = 0.032), and 30 days for patients with Gleason 8–10 and PSA 11–20 (0.041). CONCLUSION: In low‐risk disease, there is a considerable but not unlimited surgical delay which will not adversely impact the rate of adverse pathologic features found. In higher risk disease, this time period is considerably shorter. Prostate 75:1085–1091, 2015 . © 2015 Wiley Periodicals, Inc.